2015
DOI: 10.1038/srep13922
|View full text |Cite
|
Sign up to set email alerts
|

Importance of liquid fragility for energy applications of ionic liquids

Abstract: Ionic liquids (ILs) are salts that are liquid close to room temperature. Their possible applications are numerous, e.g., as solvents for green chemistry, in various electrochemical devices, and even for such “exotic” purposes as spinning-liquid mirrors for lunar telescopes. Here we concentrate on their use for new advancements in energy-storage and -conversion devices: Batteries, supercapacitors or fuel cells using ILs as electrolytes could be important building blocks for the sustainable energy supply of tomo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
106
1
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(127 citation statements)
references
References 30 publications
(90 reference statements)
18
106
1
2
Order By: Relevance
“…The relaxation times (s), which are revealed by the temperature dependent peak position of , are illustrated in an Arrhenius representation in the inset of Figure 3. The dashed line represents a Vogel-Fulcher-Tammann (VFT) function [38][39][40][41], which is extrapolated to (s) = 100 s. This point corresponds to the glass transition temperature [40,42] = 330 K revealed from (s) and agrees well with measured from DSC. The Arrhenius representation also reveals that there is no significant change in temperature dependence of around the cold crystallization (cf.…”
Section: Frequency-dependent Dielectric Properties Of "As-supporting
confidence: 69%
“…The relaxation times (s), which are revealed by the temperature dependent peak position of , are illustrated in an Arrhenius representation in the inset of Figure 3. The dashed line represents a Vogel-Fulcher-Tammann (VFT) function [38][39][40][41], which is extrapolated to (s) = 100 s. This point corresponds to the glass transition temperature [40,42] = 330 K revealed from (s) and agrees well with measured from DSC. The Arrhenius representation also reveals that there is no significant change in temperature dependence of around the cold crystallization (cf.…”
Section: Frequency-dependent Dielectric Properties Of "As-supporting
confidence: 69%
“…However, the larger differences between T g and the theoretical T o are considered to depend on the liquid fragility or strength. Furthermore, while lower values of T g would be expected to yield lower viscosity, or higher conductivity, it has been shown for ILs under ambient conditions that these properties are dependent on both fragility and T g . The concept of fragility, introduced by Angell, describes the rate at which the transport properties and relaxation dynamics of a glass‐forming material changes as the temperature approaches T g .…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, strong materials are considered more impervious to structural changes upon heating above their T g . Ionic liquids, materials known for undergoing glass transitions and commonly inadequately described by normal Arrhenius‐type temperature dependence (in terms of transport properties), have been frequently described as exhibiting intermediate to high fragility, such that their transport and relaxation dynamics change several orders of magnitude over relatively small temperature deviations close to their T g …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the energy density of LIBs leads to a greater probability of combustion; hence, non‐flammable electrolytes should be used to enhance the safety of LIBs. Ionic liquids have excellent physicochemical properties as electrolyte solvents, such as negligible vapor pressure, non‐flammability, high conductivity, and wide electrochemical windows . We have reported that a Si‐anode exhibits a better electrochemical performance in some ionic liquid electrolytes compared to that in conventional organic electrolytes .…”
Section: Introductionmentioning
confidence: 99%